Misuse of Divorce and Its Remedies in the Light of the Qur’an and Sunnah - Fozia Ayub; Dr Manzoor Ahmad Al-Azhari (Journal of Religion and Society, 2026)
Islam regards marriage as a sacred and enduring social contract intended to ensure family stability, emotional tranquility, and mutual compassion. Divorce, while legally permitted, is introduced in Islamic law only as a last resort when marital harmony becomes impossible to sustain. In contemporary society, however, the misuse and hasty application of divorce has emerged as a serious challenge to the Islamic family system. Such misuse not only causes profound psychological, social, and economic harm to women and children but also contributes to social instability and misrepresents Islamic teachings.This research article critically examines the concept of divorce, the various forms of its misuse, and the underlying causes and consequences in the light of the Qur’an and Sunnah. The study highlights that Islam discourages divorce when exercised without genuine necessity and emphasizes patience, reconciliation, and justice as foundational principles of marital life. Furthermore, the Qur’anic framework of arbitration (ḥakamayn), reconciliation, waiting periods (ʿiddah), and the Prophetic model of ethical conduct and forbearance are analyzed as effective preventive and corrective mechanisms. The article also reviews classical juristic opinions and contemporary scholarly discussions to propose practical reformative measures, including premarital counseling, family education, religious awareness, and legal and social reforms. The study concludes that adherence to the true spirit of Islamic teachings can significantly prevent the misuse of divorce and contribute to the preservation and strengthening of the Islamic family system. Keywords: Islam, Law , Family Stability, Divorce